PEMANFAATAN JURNALISTIK DAN MEDIA SOSIAL BAGI GURU DAN KARYAWAN SD IT MIFTAHUL IMAN PEKANBARU - Dailiati, Surya; Sudaryanto, Sudaryanto; Saputri, Jeni; Hernimawati, Hernimawati (Komunitas Manajemen Kompetitif, 2024)
Journalism and social media, if combined, will be even better for everyone, including those in the world of education, especially the Miftahum Iman Integrated Islamic Elementary School (SD IT MI). Moreover, SD IT MI is a private school which must have more advantages compared to state schools. The problem at SD IT Miftahul Iman is that they have never received information and outreach about journalism and social media from official institutions. Then the school community (teachers, employees and students) need to understand journalism and social media literacy needs to be improved. The method of implementing community service is carried out by means of counseling and discussion, pre-test and post-test. The service carried out at SD IT Miftahul Iman provides/increases the understanding of teaching staff and educational staff about journalism and social media. For journalism, so far they can only enjoy it directly by reading, hearing and watching what is in print and electronic media. Teachers and educational staff already have knowledge and use of social media. However, the narrative regarding the use of social media needs to be improved to be better in quality and quantity. Keywords: Utilization, Journalism, Medi, Social, School